PENERAPAN TEKNOLOGI PEMUPUKAN PADI SAWAH DI PROVINSI BENGKULU - Astuti, Herlena Bidi; Wibawa, Wahyu (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
Fertilizing is one of strategy to improve crops productivity because it provides nutrient for the plant. This paper aims to analyze the implementation of fertilizing technology for field rice. The study was conducted from May-July 2012 in four districts that were North Bengkulu, Central Bengkulu, South Bengkulu and Kepahiang. Data was collected by survey method using questionnaire to 261 respondents. Statistic analysis using Chi quadrate was used to analyze most frequent fertilizer farmer use. The study showed farmers prefer five fertilizers. The implementation of these five fertilizers was varied.majority of respondents (95%) used urea. The second preferred fertilizer was NPK (67.8%), followed by TSP (59.7%), KCL (46.3%) and organic fertilizer (34.8%). Implementation of organic fertilizer was highest in Kepahiang and South Bengkulu that also show highest land productivity